Pseudo-3D aerostatic instability analysis of suspension bridge deck using finite volume solution of wind flow and Element-Free Galerkin of structure. (June 2021) - Zamiri, Golriz; Sabbagh-Yazdi, Saeed-Reza
Abstract: This study proposes a new approach for modeling fluid–structure interaction (FSI) in suspension bridges subjected to wind-induced forces. The approach is based on coupling the Element-Free Galerkin (EFG) method with Finite Volume Method (FVM), which are used to establish the numerical model of the structural components of the bridge and wind flow around the bridge deck, respectively. In the proposed approach, the commercial Computational Fluid Dynamic (CFD) code of ANSYS FLUENT software for FVM solution of the wind flow simulation is linked to a MATLAB code for the EFG analysis of the bridge structure. Regarding the fluid domain, the turbulent wind flow simulation around the moving bridge deck is idealized as a set of stacked two-dimensional planes around deck section, whereas the bridge deck is idealized by some sequential 1D longitudinal EFG sub-domains and EFG 1D sub-domains are adopted for the cables and hangers of the suspension bridge in a three-dimensional space. Despite the methods utilized by previous models of wind flow around deck sections, the pseudo-3D methodology adopted in the present paper is based on changing the angle of attack of the wind at the inlet far-field boundary and therefore, a fixed computational fluid domain is considered. This implies that the torsional deformations of the nodes of the bridge deck are regarded as the wind's angle of attack at inlet part of the far-field boundaries which leads to a variable inlet flow velocity. This eliminates the need for progressive mesh regeneration and consequently, reduces the computational cost. The performance of the proposed approach is assessed in terms of predicting the aerostatic instability limit of a long-span suspension bridge case study. According to the analysis results, the proposed approach satisfactorily estimates the critical wind velocity for aerostatic instability and the results are in good agreement with the previous studies. The proposed semi-3D strategy has shown to be computationally efficient in capturing the aerostatic behavior of suspension bridges in 3D space under 2D wind flow around deck sections and can be effectively used to determine the instability limit of such systems without compromising the accuracy of the results.